Development : A Coin with Two Sides - Wolfensohn, James D. (International Herald Tribue, 2017)
James D. Wolfensohn, President of the World Bank Group, writes that development economics is the discipline that addresses the world's most enduring problem: persistent and widespread poverty. Within this deprivation is another dimension: hundreds of millions of girls and women whose lives are diminished and shortened by inadequate economic means and discrimination in social status and medical attention. The end of the cold war has been accompanied by a growing recognition of the importance of political, social, and economic participation, by widespread demands for human rights and gender equity, and by an emerging globalized economy. This offers an unprecedented opportunity to make development work. There is a need for effective and impartial legal and justice systems, with protection of and positive support for rights and freedoms of various kinds, a well-organized and supervised financial system, effective social safety nets, and essential social programs.